Quality standards for medicines in Ukraine - Buchkova, Tetiana (Actual Problems of Medicine and Pharmacy, 2021)
The article defines the main goal, level, main tasks and objects of standardization. Depending on the specifics of the object of standardization, there are seven types of standards: fundamental, standards for testing methods, products, processes, services, compatibility of products, services or systems with their joint use, general technical specifications. It was established that the quality of medicines in Ukraine is regulated by the State Pharmacopoeia of Ukraine; Laws of Ukraine "On Medicines" and "On Protection of Consumer Rights"; good practice guidelines; Orders of the Ministry of Health of Ukraine; Decisions of the Cabinet of Ministers of Ukraine; ISO 9000 standards.